KLASIFIKASI KEMAMPUAN LAHAN DI KAWASAN KABUPATEN MANOKWARI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Brenda Fonataba; Prima Jiwa Osly; Irfan Ihsani (Jurnal Infrastruktur, 2020)
The Land is a natural resource that has limitations to accommodate human activities in land use. Utilization of land for residential land, regional development or, other land uses sometimes creates many environmental problems such as degradation of land quality and disturbance of natural balance. The increasing need for and competition in land use for regional development in Manokwari Regency requires careful thought in making decisions about the most beneficial use of limited land resources. Land Capability Classification is directed to determine the potential of land for broad land use based on suitable methods of use. The research variables used are nine Land Capability Units (LCU), namely LCU Morphology, LCU Slope Stability, LCU for Foundation Stability, LCU Water Availability, LCU Ease of Doing, LCU Against Erosion, LCU for Waste Disposal, LCU for Drainage and LCU for Natural Disasters. All LCU are analyzed using input in the form of factors limiting land capability consisting of maps of elevation, slope, soil type, rainfall, watershed, geology, natural disasters, and land use. The analysis produces an output in the form of a land capability classification map from the results of the digital spatial analysis process using a Geographical Information System (GIS).